Adsorption of chlorinated solvents in nonionic surfactant solutions with activated carbon in a fixed bed - Yang, Jung-Seok; Baek, Kitae; Kwon, Tae-Soon; Yang, Ji-Won (ELSEVIER SCIENCE INC, 2009)
The adsorption characteristics of chlorinated solvents, trichloroethylene (TCE) and perchloroethylene (PCE), in surfactant solutions with granular activated carbon (GAC) were investigated with the goal of recovering the surfactant from the effluent in surfactant enhanced remediation (SER). Triton X-100 (TX100) and X-165 (TX165) were selected as model surfactants, and the GAC was Darco 20-40. The adsorption amounts for the TX100 and TX165 onto GAC was about 0.26-0.27 g/g GAC. On a GAC fixed bed, the adsorbed amounts of TCE (0.19 g/g) and PCE (0.35 g/g) in the TX165 (10g/L) solution onto the GAC were higher than those for TCE(0.16 g/g)and PCE (0.24 g/g) in the TX100 (10 g/L) solution. Because the ratio of surfactants/chlorinated solvents in the ordinary effluent of SER is higher than 1, activated carbon adsorption could be used as an alternative of post-treatment method in SER. (C) 2009 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: ORGANIC-COMPOUNDS; SELECTIVE ADSORPTION; AQUEOUS-SOLUTION; REMOVAL; WATER; REMEDIATION; TRICHLOROETHYLENE; ULTRAFILTRATION; PHENANTHRENE; ISOTHERMS